Brand Awareness Among Consumers In Malaysia: A Study On Halal Branding - Mohammad Noorizzuddin Nooh; Norhaziah Nawai; Nuradli Ridzwan Shah Mohd Dali; Hartini Mohammad (Universiti Sains Islam Malaysia, 2024)
Since Malaysia is heading towards being a global Halal hub, this research is very crucial to give ideas on the receptions of Muslim consumers towards Halal branding. The objectives of the research are to measure the awareness of consumers towards Halal products particularly in the food product line, to determine whether the Halal logo has any influence in consumer purchase decision, to determine whether religion has any influence in purchasing Halal food products, to identify the relationship between brand image and the existence of Halal logo with the customer's purchase decisions, and to identify the relationship between price and the existence of Halal logo with the customer's purchase decision. A survey was conducted on selected 1075 samples from Johor, Malacca, Selangor, Negeri Sembilan, Kuala Lumpur, Perak, Penang, and Pahang. In terms of research tools, the researchers use descriptive analysis to analyze the frequency of each variable, factor analysis to reduce the number of variables and to detect structure in the relationship between the variables or to classify the variables, mean to measure the awareness of consumers towards halal products. For further analysis this study applied the Chi-square to determine whether the Halal certification has any influence in consumer purchase decision. ANOVA is used to determine whether religion has any influence in purchasing Halal food products. A correlation analysis is being done to analyze the relationship between variables such as brand image and price and the existence of Halal certification with the customer's purchase decisions. One significant finding is that the respondents agree that Halal products are for everybody and not only confined to Muslims consumption. Apart from that, they also believe that the Halal certification should not only be given to companies owned by Bumiputera. On the manufacturers' side, they have to improve the quality, design and packaging as well as adding values to their current products. On the government side, they have impose stricter regulation regarding Halal certification and also make grants available to Muslim entrepreneurs in terms of product development.